Navigating higher education during COVID-19: a systematic review and meta-analysis of NPS and customer experience in technological adoption - Sergio Pardo-Jaramillo; Daniel Aristizábal-Hernández; Paulo Cabrera; Ignacio Osuna Soto; Andres Muñoz-Villamizar (Humanities & Social Sciences Communications)
Abstract The accelerated shift to digital learning in higher education, driven by the COVID-19 pandemic, significantly impacted student satisfaction and technology adoption. Utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, this systematic review and meta-analysis assesses the impact of this transition on student satisfaction, measured through the Net Promoter Score (NPS). Analysis across multiple educational programs reveals that postgraduate programs focused on educational innovation received a more favorable response to technological integration compared to undergraduate programs, which demonstrated lower NPS scores and encountered greater adaptation challenges. The findings highlight the necessity of conducting experimental research to further understand causal relationships between technology use and student satisfaction, considering diverse academic contexts, pedagogical strategies, and accessibility of resources. This research advances the discourse on digital transformation in education by emphasizing the importance of tailored technology-mediated strategies that address diverse student needs.